2019
DOI: 10.15537/smj.2019.2.23872
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vancomycin utilization among Lebanese hospitals

Abstract: Objectives: To assess the appropriateness of vancomycin dosing and monitoring at Lebanese hospitals. Methods: This was a multicenter retrospective study conducted at 3 Lebanese hospitals between January and March 2018. Patients 18 years of age and older treated with vancomycin for a systemic infection or prophylaxis were eligible for study enrollment. Consistency with the Infectious Diseases Society of America guidelines was evaluated to determine whether the dose of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Publications indicate that in critically ill patients, vancomycin concentrations often do not reach therapeutic levels (15-20 mg/L) during the first 5 days of vancomycin therapy [17]. For more successful therapy results, vancomycin concentration should reach therapeutic concentration more rapidly [18]. Malaeb et al (2019) reported that most of the physicians do not administer a loading dose when initiating vancomycin therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Publications indicate that in critically ill patients, vancomycin concentrations often do not reach therapeutic levels (15-20 mg/L) during the first 5 days of vancomycin therapy [17]. For more successful therapy results, vancomycin concentration should reach therapeutic concentration more rapidly [18]. Malaeb et al (2019) reported that most of the physicians do not administer a loading dose when initiating vancomycin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For more successful therapy results, vancomycin concentration should reach therapeutic concentration more rapidly [18]. Malaeb et al (2019) reported that most of the physicians do not administer a loading dose when initiating vancomycin therapy. This could explain why in most of the cases target vancomycin concentration levels cannot be achieved [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation